PERLINDUNGAN HUKUM TERHADAP CONTENT CREATOR FACEBOOK PROFESIONAL DALAM MENDAPATKAN MONETISASI DARI KREATIVITASNYA - NIM. A1011221041, EQRI FERDIANSYAH (Jurnal Fatwa Hukum, 2025)
Abstract The development of social media platforms has created new economic opportunities for content creators through digital monetization, particularly on Facebook Professional. However, these opportunities are accompanied by legal challenges, especially content theft or freebooting, which causes economic losses and violates creators’ copyright. This article aims to analyze the forms of legal protection available for Facebook Professional content creators in obtaining monetization and to identify the obstacles faced in its implementation. This research employs an empirical legal method with a normative approach by examining relevant legislation and supported by field data obtained through interviews with Facebook Professional content creators. The legal framework analyzed includes Law Number 28 of 2014 on Copyright, Law Number 11 of 2008 as amended by Law Number 19 of 2016 on Electronic Information and Transactions, Government Regulation Number 71 of 2019, and Minister of Communication and Informatics Regulation Number 5 of 2020. The findings indicate that, normatively, Indonesian law has provided legal protection through the recognition of moral and economic rights, as well as criminal sanctions against copyright infringement. Nevertheless, in practice, such protection has not been optimally realized due to low legal awareness among content creators, complex formal legal procedures, weak law enforcement, and limitations of platform-based reporting mechanisms. This study contributes to the legal literature by highlighting the gap between normative legal protection and empirical reality, emphasizing the need for enhanced legal literacy, stronger law enforcement, and greater responsibility from digital platforms to ensure effective protection of creators’ rights in the digital economy. Keywords: legal protection, Content Creator, Facebook Profesional, monetization, copyright Abstrak Perkembangan media sosial telah menciptakan peluang ekonomi baru bagi Content Creator melalui program monetisasi digital, khususnya pada fitur Facebook Profesional. Namun, peluang tersebut juga diiringi dengan permasalahan hukum, terutama pencurian konten (freebooting) yang menimbulkan kerugian ekonomi dan melanggar hak cipta pencipta. Artikel ini bertujuan untuk menganalisis bentuk perlindungan hukum bagi Content Creator Facebook Profesional dalam memperoleh monetisasi serta mengidentifikasi kendala yang dihadapi dalam implementasinya. Penelitian ini menggunakan metode hukum empiris dengan pendekatan normatif melalui kajian peraturan perundang-undangan yang relevan serta didukung oleh data lapangan berupa wawancara dengan Content Creator Facebook Profesional. Kerangka hukum yang dianalisis meliputi Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta, Undang-Undang Nomor 11 Tahun 2008 juncto Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik, Peraturan Pemerintah Nomor 71 Tahun 2019, serta Peraturan Menteri Komunikasi dan Informatika Nomor 5 Tahun 2020. Hasil penelitian menunjukkan bahwa secara normatif hukum Indonesia telah memberikan perlindungan melalui pengakuan hak moral dan hak ekonomi serta sanksi pidana terhadap pelanggaran hak cipta. Namun, secara empiris perlindungan tersebut belum berjalan optimal karena rendahnya kesadaran hukum Content Creator, kompleksitas prosedur hukum formal, lemahnya penegakan hukum, serta keterbatasan mekanisme pelaporan pada platform digital. Artikel ini berkontribusi dalam literatur hukum dengan menegaskan adanya kesenjangan antara pengaturan hukum dan praktik di lapangan serta menekankan pentingnya peningkatan literasi hukum, penguatan penegakan hukum, dan tanggung jawab platform digital dalam melindungi hak Content Creator di era ekonomi digital. Kata kunci: perlindungan hukum, Content Creator, Facebook Profesional, monetisasi, hak cipta